2018
DOI: 10.1080/1061186x.2017.1419363
|View full text |Cite
|
Sign up to set email alerts
|

Translation of combination nanodrugs into nanomedicines: lessons learned and future outlook

Abstract: The concept of nanomedicine is not new. For instance, some nanocrystals and colloidal drug molecules are marketed that improve pharmacokinetic characteristics of single-agent therapeutics. For the past two decades, the number of research publications on single-agent nanoformulations has grown exponentially. However, formulations advancing to pre-clinical and clinical evaluations that lead to therapeutic products has been limited. Chronic diseases such as cancer and HIV/AIDS require drug combinations, not singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 99 publications
0
16
0
Order By: Relevance
“…As mentioned above, the NEs systems could be prominently delivering poorly soluble antiviral agents [ 69 , 70 ] as a result of extensive lymphatic absorption. The in vivo murine study revealed 11.5 fold increase in the bioavailability of baicalin (a flavonoid used to treat viral hepatitis) in lymph nodes when delivered with a nanoemulsion carrier [ 71 ].…”
Section: Essential Oil-based Nes/mes Antiviral and Drug Delivery Systmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, the NEs systems could be prominently delivering poorly soluble antiviral agents [ 69 , 70 ] as a result of extensive lymphatic absorption. The in vivo murine study revealed 11.5 fold increase in the bioavailability of baicalin (a flavonoid used to treat viral hepatitis) in lymph nodes when delivered with a nanoemulsion carrier [ 71 ].…”
Section: Essential Oil-based Nes/mes Antiviral and Drug Delivery Systmentioning
confidence: 99%
“…Additionally, a single NEs system could accommodate the water-soluble drugs such as the nucleoside and nucleotide analogues of the anti-HIV drug (e.g. tenofovir) and highly water-insoluble drugs (e.g., raltegravir or paclitaxel) and exhibit targeted and long-acting characteristics in vivo [ 70 ].…”
Section: Essential Oil-based Nes/mes Antiviral and Drug Delivery Systmentioning
confidence: 99%
“…The issue of removal processes of inorganic nanoparticles from the circulation consequents to discharging their beneficial effects and the lack of biological breakdown/metabolic mechanism, contrasting to most liposomes and polymeric nanoparticles. Hence, there is need for investigation into the effects of chronic use of inorganic nanoparticles on biological activities of the body especially at the cellular and molecular level [60,61]. Inorganic nanoparticles like gold nanoparticles have been used in management of cancer, diabetes, arthritis, and heart and Alzheimer's diseases.…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%
“…More detailed discussions of a working hypothesis can be found in these recent papers [61,137,138]. Reviews by our group describe some important results obtained with lipid nanoparticles for drug delivery to lymph nodes and have further discussion on relevant targeting mechanisms [139][140][141].…”
Section: Lymph Nodesmentioning
confidence: 99%